2012
DOI: 10.1021/jm2016182
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Mechanism of Action and Enzymatic Selectivity of Psammaplin A against Its Epigenetic Targets

Abstract: Psammaplin A (11c) is a marine metabolite previously reported to be a potent inhibitor of two classes of epigenetic enzymes: histone deacetylases and DNA methyltransferases. The design and synthesis of a focused library based on the psammaplin A core has been carried out to probe the molecular features of this molecule responsible for its activity. By direct in vitro assay of the free thiol generated upon reduction of the dimeric psammaplin scaffold, we have unambiguously demonstrated that 11c functions as a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 77 publications
(180 reference statements)
6
87
0
Order By: Relevance
“…More recently, it has been shown to inhibit proliferation of several cancer lines at nanomolar concentrations and with a low cytotoxicity through selective induction of genes related to cell cycle arrest and apoptosis (Ahn et al, 2008;Kim et al, 2007;Piña et al, 2003). Several studies have found PsA to be a potent inhibitor of HDACs in vitro (Kim et al, 2007;Piña et al, 2003), specifically of HDAC1 (Baud et al, 2012), and to induce the accumulation of highly acetylated H3 in treated HeLa cells (Kim et al, 2007). Piña et al (2003) also reported a potent DNMTi activity of PsA in vitro in addition to its HDACi activity, but later studies found no evidence for this dual action (Baud et al, 2012;García et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown to inhibit proliferation of several cancer lines at nanomolar concentrations and with a low cytotoxicity through selective induction of genes related to cell cycle arrest and apoptosis (Ahn et al, 2008;Kim et al, 2007;Piña et al, 2003). Several studies have found PsA to be a potent inhibitor of HDACs in vitro (Kim et al, 2007;Piña et al, 2003), specifically of HDAC1 (Baud et al, 2012), and to induce the accumulation of highly acetylated H3 in treated HeLa cells (Kim et al, 2007). Piña et al (2003) also reported a potent DNMTi activity of PsA in vitro in addition to its HDACi activity, but later studies found no evidence for this dual action (Baud et al, 2012;García et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found PsA to be a potent inhibitor of HDACs in vitro (Kim et al, 2007;Piña et al, 2003), specifically of HDAC1 (Baud et al, 2012), and to induce the accumulation of highly acetylated H3 in treated HeLa cells (Kim et al, 2007). Piña et al (2003) also reported a potent DNMTi activity of PsA in vitro in addition to its HDACi activity, but later studies found no evidence for this dual action (Baud et al, 2012;García et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The reduced products were prepared by in situ reduction of the respective disulfides using TCEP and used immediately (using the same agent and a similar method to that reported by Baud et al 35 ). (C) Proposed mechanisms for the release of SAHA: the first is direct cleavage of the ester linkage to generate the parent drug by intracellular esterases; the second involves reduction of the disulfide linkage and intramolecular cyclization; (a similar reaction mechanism has been reported by Zhang et al 55 and Wu et al 56 ) the third is the reduction of the disulfide linkage, followed by cleavage of ester linkage.…”
Section: ) (B)mentioning
confidence: 99%
“…HDACs came from HeLa cell nucleus extracts, mainly including HDAC1 and HDAC2, and the substrate was an acetylated histone peptide. The required stock solution of thiol was prepared and used immediately prior to assay from the corresponding disulfide analogs using 1.5 equiv tris(2-carboxyethyl)phosphine hydrochloride (TCEP) as the reducing agent, in a 9:1 DMSO/water solution according to the general procedure described by Baud et al 35 Stock solutions of test compounds and the control drug SAHA were diluted to various concentrations. On the 96-well plate, HDACs (15 µL/well) were incubated at 37°C with 10 µL of various concentrations of samples and 25 µL of substrate.…”
mentioning
confidence: 99%
“…76 Psammaplin A (11c), a marine metabolite, was noted to be highly effective against HDAC1. 77 Cell cycle control genes Methylation of cell cycle control genes can also be modulated by natural products. For example, an aqueous extract of Opuntia ficus indica, and its bioactive ingredient, betalain indicaxanthin, reportedly induced demethylation of cyclindependent kinase inhibitor 2A (p16; INK4A; CDKN2A) which is a tumor suppressor gene.…”
Section: Hdac Inhibitorsmentioning
confidence: 99%